Water, power, homeland: restoring and re-storying the Eklutna River - Middleton Manning, Beth Rose (Frontiers in Human Dynamics, 2023)
Beginning in 1929, the Eklutna River in southcentral Alaska was largely de-watered for hydropower production without the consent of the Eklutna Dena’ina people. The hydropower projects were implemented in two waves—first in 1929 by a private developer and then in 1951 by the Bureau of Reclamation. In 1991, a Fish and Wildlife Agreement between the utilities, the State of Alaska, and federal agencies called for study of the impacts of the hydroelectric projects on fish and wildlife, and development of a mitigation plan by 2024. This paper examines the process and partners involved in advocating for restoration of the Eklutna, building on the documented importance of tribal leadership in dam removals, and centering three factors that are underrepresented in the current analyses of alternative management approaches to the Eklutna: the context of the Eklutna as a Dena’ina place; the egregious and ongoing Indigenous environmental injustice of seizing Eklutna water; and the praxis of Dena’ina-led efforts to find a balance of uses of this highly valued Dena’ina watershed.